Photometry and long-slit spectroscopy of the split comet C/2019 Y4 (ATLAS). Issue 4 (16th September 2021) - Ivanova, Oleksandra; Luk'yanyk, Igor; Tomko, Dušan; Moiseev, Alexei
ABSTRACT: We present an analysis of the photometric and spectroscopic observations of the split comet C/2019 Y4 (ATLAS). Observations were carried out on 2020 April 14 and 16, when the heliocentric distance of the comet was 1.212 and 1.174 au, its geocentric distance 0.998 and 0.991 au, and the phase angle 52.°9 and 54.°5, respectively. The comet was observed with the 6-m BTA (Big Telescope Alt-azimuth) telescope of the Special Astrophysical Observatory (Russia) with the SCORPIO-2 (Spectral Camera with Optical Reducer for Photometric and Interferometric Observations) multimode focal reducer. The narrow-band BC and RC cometary filters in the continuum were used. We identified numerous emissions of CN, C2, C3, and NH2 molecules within the range of 3750–7100 Å. The C2 /CN and C3 /CN production rate ratios coincide with those of typical comets. Four fragments belonging to the coma were detected in both observational runs. We compared and analysed temporal variations of the visual magnitudes, gas productivity, and dust colour. Based on our dynamical investigation of the orbits of comets C/1844 Y1 (Great comet) and C/2019 Y4 (ATLAS), we can claim that, with high probability, the two comets do not have a common progenitor.